Scheduling construction projects with resources accessibility limited and changeable in time - Jaśkowski, Piotr; Sobotka, Anna (Journal of Civil Engineering and Management, 2004)
This paper aims at solving the problem of minimising the construction project duration in deterministic conditions when the accessibility of renewable resources is limited and changeable in time (workforce, machines and equipment). Particular construction processes (with various levels of complexity) must be conducted in the established technological order and can be executed in different technological and organisational variants (different contractors, technologies, and ways of using resources). To solve this problem the authors are using evolutionary algorithm. For the assessment of solutions generated by evolutionary algorithm, the authors have worked out a heuristic algorithm (of resources allocation and project duration calculation). This methodology seems to produce similar outcomes when juxtaposed with other solutions obtained by research works carried out using comparable methodologies. The paper contains an example of practical application of evolutionary algorithm for construction project planning within resources and time constraints.First Published Online: 14 Oct 2010